Assessing viability of extracorporeal preserved muscle transplants using external field stimulation: a novel tool to improve methods prolonging bridge-to-transplantation time. - Taeger, Christian; Friedrich, Oliver; Dragu, Adrian; Weigand, Annika; Hobe, Frieder; Drechsler, Caroline; Geppert, Carol-Immanuel; Arkudas, Andreas; Münch, Frank; Buchholz, Rainer; Pollmann, Charlotte; Schramm, Axel; et al. (Scientific Reports, 2015)
Preventing ischemia-related cell damage is a priority when preserving tissue for transplantation. Perfusion protocols have been established for a variety of applications and proven to be superior to procedures used in clinical routine. Extracorporeal perfusion of muscle tissue though cumbersome is highly desirable since it is highly susceptible to ischemia-related damage. To show the efficacy of different perfusion protocols external field stimulation can be used to immediately visualize improvement or deterioration of the tissue during active and running perfusion protocols. This method has been used to show the superiority of extracorporeal perfusion using porcine rectus abdominis muscles perfused with heparinized saline solution. Perfused muscles showed statistically significant higher ability to exert force compared to nonperfused ones. These findings can be confirmed using Annexin V as marker for cell damage, perfusion of muscle tissue limits damage significantly compared to nonperfused tissue. The combination of extracorporeal perfusion and external field stimulation may improve organ conservation research.

Hydroxyethyl starch solution for extracorporeal tissue perfusion - Taeger, Christian; Friedrich, Oliver; Drechsler, Caroline; Weigand, Annika; Hobe, Frieder; Geppert, Carol-Immanuel; Münch, Frank; Birkholz, Torsten; Buchholz, Rainer; Horch, Raymund E.; Präbst, Konstantin; Buchholz, Rainer (Clinical hemorheology and microcirculation, 2016)
In the field of free flap transfer in reconstructive surgery, the trans- or replanted tissue always undergoes cell damage during ischemia to a more or less strong extent. In previous studies we already showed that conserving muscle transplants by means of extracorporeal perfusion over a period of 6 hours by using a crystalloid solution for perfusion. However, we observed significant edema formation. In this study we aimed at reducing the edema formation by using an iso-oncotic colloid as perfusion solution. This way we want to evaluate a possible new application of hydroxyl-ethyl starch in an extracorporeal setup to exploit potential benefits of the colloid.Examined parameters include the muscles' functionality with external field stimulation, histological examination and edema formation. Perfused muscles showed a statistically significant higher ability to exert force compared to nonperfused ones. These findings can be confirmed using Annexin V as marker for cell damage, perfusion of muscle tissue limits damage significantly compared to nonperfused tissue. Substituting the electrolyte perfusion solution with a colloidal one shows the tendency to reduce the edema formation but without statistical significance.